Dissemination of Mathematics Learning Media Products in Gugus VII Elementary Schools at South Kuta District - I Kadek Budi Sandika; Komang Kurniawan Widiartha; I Gede Adi Sudi Anggara; I Nengah Arnawa; I Putu Wisnu Aji Bagaskara; Adhi Firdaus (Abdimas Paspama, 2023)
Elementary schools in Pecatu Village, which are part of Gugus VII in South Kuta Subdistrict, face inequities in the number of students. Schools in densely populated areas have more students, while those in quiet areas have fewer students, impacting on the acquisition of operational funds and the limited allocation of funds for the development of learning facilities. The main problem is the lack of variety in mathematics learning media. The solution is product dissemination to mathematics teachers in Gugus VII, involving socialization, training, and evaluation. Implementation began in July 2023 with team introductions and implementation agreements. Dissemination and training activities were carried out in August 2023, involving 18 participants from six schools. The evaluation showed the partners' appreciation of the product, with the school principal's hope that the activities would continue continuously and could be developed according to the needs of each school. Feedback from students highlighted the desire for comedic or humorous nuances in animation-based learning video content. Student assessment results showed positive acceptance, with 69% strongly agreeing, 26% agreeing, and 5% being less affected by the media.